2015
DOI: 10.1155/2015/578423
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection, Infertility, and Assisted Reproductive Outcomes

Abstract: The human papillomavirus (HPV) is a sexually transmitted infection common among men and women across all geographic and socioeconomic subgroups worldwide. Recent evidence suggests that HPV infection may affect fertility and alter the efficacy of assisted reproductive technologies. In men, HPV infection can affect sperm parameters, specifically motility. HPV-infected sperm can transmit viral DNA to oocytes, which may be expressed in the developing blastocyst. HPV can increase trophoblastic apoptosis and reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 84 publications
1
46
0
3
Order By: Relevance
“…The results of this systematic review and meta-analysis are in accordance with those of other reviews. Noventa et al 31 , Pereira et al 32 and Souho et al 33 in their reviews investigating the impact of HPV on infertility, IVF failure and pregnancy outcomes, employing data from some of the studies presented here, showed conflicting results or no correlation. Importantly, Souho et al 33 indicated that factors with a potentially negative impact include cervical HPV-induced cytological lesions and eventual changes in fetal health.…”
Section: Discussionmentioning
confidence: 71%
“…The results of this systematic review and meta-analysis are in accordance with those of other reviews. Noventa et al 31 , Pereira et al 32 and Souho et al 33 in their reviews investigating the impact of HPV on infertility, IVF failure and pregnancy outcomes, employing data from some of the studies presented here, showed conflicting results or no correlation. Importantly, Souho et al 33 indicated that factors with a potentially negative impact include cervical HPV-induced cytological lesions and eventual changes in fetal health.…”
Section: Discussionmentioning
confidence: 71%
“…In women, HPV is capable of causing difficulty in conception and abortions through reduction of endometrial implantation of throphoblastic cells (17,18). In males, HPV is associated with altered sperm motility (17,19,20). With these in mind, one would have expected a strong association between cervical neoplasia and female infertility in our study.…”
Section: Discussionmentioning
confidence: 73%
“…Though the mechanism is not yet understood, recent studies are showing that HPV is associated with altered fertility. In women, HPV is capable of causing difficulty in conception and abortions through reduction of endometrial implantation of throphoblastic cells (17,18). In males, HPV is associated with altered sperm motility (17,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Sexually transmitted infections such as Chlamydia trachomatis , Neisseria gonorrhoeae, and HPV may affect fertility or reproductive outcomes [36, 37]. Our meta-analysis results showed that there was no significant association between HPV infection and pregnancy rate of ART, with a pooled RR of 1.04 (95% CI 0.64–1.70).…”
Section: Discussionmentioning
confidence: 82%